Mechanistic failure mode investigation and resolution of parvovirus retentive filters. (3rd June 2016) - LaCasse, Daniel; Lute, Scott; Fiadeiro, Marcus; Basha, Jonida; Stork, Matthew; Brorson, Kurt; Godavarti, Ranga; Gallo, Chris
Abstract : Virus retentive filters are a key product safety measure for biopharmaceuticals. A simplistic perception is that they function solely based on a size‐based particle removal mechanism of mechanical sieving and retention of particles based on their hydrodynamic size. Recent observations have revealed a more nuanced picture, indicating that changes in viral particle retention can result from process pressure and/or flow interruptions. In this study, a mechanistic investigation was performed to help identify a potential mechanism leading to the reported reduced particle retention in small virus filters. Permeate flow rate or permeate driving force were varied and analyzed for their impact on particle retention in three commercially available small virus retentive filters. © 2016 American Institute of Chemical Engineers Biotechnol. Prog ., 32:959–970, 2016